Contribution Analysis (Better Evaluation)
Contribution Analysis is an approach for assessing causal questions and inferring causality in real-life program evaluations. It offers a step-by-step approach designed to help managers, researchers, and policymakers arrive at conclusions about the contribution their program has made (or is currently making) to particular outcomes. The essential value of contribution analysis is that it offers an approach designed to reduce uncertainty about the contribution the intervention is making to the observed results through an increased understanding of why the observed results have occurred (or not!) and the roles played by the intervention and other internal and external factors. Contribution analysis is particularly useful in situations where the programme is not experimental, i.e. not in trial projects but in situations where the programme has been funded on the basis of a relatively clearly articulated theory of change and where there is little or no scope for varying how the program is implemented. Contribution analysis helps to confirm or revise a theory of change; it is not intended to be used to surface or uncover and display a hitherto implicit or inexplicit theory of change. The report from a contribution analysis is not definitive proof, but rather provides evidence and a line of reasoning from which we can draw a plausible conclusion that, within some level of confidence, the program has made an important contribution to the documented results.